Disordered violence: how gender, race and heteronormativity structure terrorism - Gentry, Caron E. (Advances in critical military studies, 2020)
Intro -- Half Title -- Series -- Title Page -- Dedication -- Copyright -- Contents -- Acknowledgements -- Introduction: Welcome to the Grey -- 1. The Structural Signification of Terrorism -- 2. Intersecting Terrorism Studies -- 3. Strange Bedfellows: What Happens When We Ask the Other Question? -- 4. Ir/rationality: Radicalisation, 'Black Extremism' and Prevent Tragedies -- 5. What Does Not Get Counted: Misogynistic Terrorism -- Conclusion: Disordered Violence -- Index